Law Enforcement Against Exhaust Modification Violations Racing on Motorcycles in Ponorogo Regency - Ardian Pratama Putra; Hananto Widodo (NOVUM : JURNAL HUKUM, 2024)
Modification of motorized vehicles today is done by many people in Indonesia. One of them is modifying the exhaust by replacing it with a racing exhaust. Vehicle modifications are still allowed but must be in accordance with the corridors of the provisions of Law Number 22 of 2009 concerning Road Traffic and Transportation, namely meeting technical standards and roadworthiness. The use of racing exhausts that do not meet the rules can be subject to action by the police, especially in the Ponorogo Resort Police area. On this basis, this study reviews how law enforcement against racing exhaust users in the Ponorogo Resort Police Region and looks for obstacles to law enforcement against racing exhaust. This research is Juridical-Empirical research by looking at legal phenomena obtained by field interviews combined with legal documents. The results obtained show that Law Enforcement in the Ponorogo Resort Police Area uses Law number 22 of 2009 concerning Road Traffic and Transportation with the main provisions using the sound level as stipulated in the National Police Telegram Letter ST/1045/V/HUK.6.2/2021 and noise level rules in accordance with the Minister of Forestry and Environment Regulation Number 7 of 2009 concerning the noise threshold of new type vehicles. Then for obstacle factors influenced by Law Enforcement Factors, Community Factors and Facilities and Infrastructure Factors.